Dispreferred Responses in Arabic Political TV Programmes - Rosly, Hakim; Alfahad, Abdulrahman (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Previous studies in Conversation Analysis (CA) have argued that the duration and structure of preferred responses differ from that of dispreferred responding actions, as the former is delivered more rapidly. Agreement responses, for instance, occur relatively quickly and take a simple form. In contrast, disagreement responses are characteristically delayed through audible breathing, silence, prefaced hesitations, appreciations, apologies, or justifications. Nevertheless, the paper focuses on a specific interactional environment where dispreferred responses are expressed directly and rapidly. It selects from a wealth of data, consisting of 12 recorded and transcribed Arabic TV programs drawn from 4 different Arabic broadcast channels. Our result shows that disagreement responses tend to be expressed explicitly and aggravatedly without alleviation or delay. The overall difference in time is insignificant and is therefore unaligned with the fundamental insight of preference organization in CA. The results can also be extended to understanding Arabic interactions, where agreement or disagreement may occur, such as in Arabic language classes, where students are expected to interact in Arabic.